EXAFS and XRD analyses of the structural evolutions involved during drying of SnO2 hydrogels - Briois, Valérie; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Brito, Giancarlo E.S. [UNESP] (Elsevier, 1995)
In order to determine structural changes during drying of inorganic gels, the local and long-range order structure of SnO2-x(OH)2x xerogels resulting from drying hydrogels with different concentrations of electrolyte (Cl- and NH+ 4) have been measured by extended X-ray absorption fine structure (EXAFS), X-ray diffraction (XRD) and N2 adsorption techniques. EXAFS measurements performed at the Sn K edge on the hydrogels and xerogels show the existence of microcrystallites with the cassiterite structure. Two drying modes have been used: freeze drying and drying by evaporation at 45°C. It is shown that the microcrystallite size determined by XRD and EXAFS techniques on the drying mode and on the electrolyte concentrations. The microcrystallite size measured on the freeze dried xerogels is similar to that of their parent hydrogels, whatever the concentration of electrolyte; however, during drying by evaporation, a preferential growth of microcrystallites along the c-axis of the cassiterite structure is observed. The size of these crystallites is enhanced with a decrease of the electrolyte concentration. Specific surface areas calculated by the Brunauer-Emmett-Teller method indicate that this preferential growth is related to the improvement of the network connectivity. The comparison of both drying processes indicates that crystallization and polycondensation are independent phenomena. © 1995 Elsevier Science B.V. All rights reserved.